Environmental History of Marine Mammal Exploitation in Trinidad and Tobago, W.I., and its Ecological Impact. (1st August 2002) - Romero, A.; Baker, R.; Cresswell, J.E.; Singh, A.; McKie, A.; Manna, M.
Abstract : Marine mammal exploitation has been documented for the Caribbean in recent times for only a handful of countries. Based on those studies a complex image of how that exploitation has taken place has begun to emerge. In order to fully understand whaling, dolphin fisheries, and manatee hunting, we still need to ascertain patterns of exploitation for many of the island-nations in that part of the world. We present a comprehensive analysis of marine mammal utilisation for Trinidad and Tobago. Trinidad and Tobago has been characterised by land-based whaling, organised during most of the nineteenth century by local elites. Dolphin fisheries have been rare and restricted to by-catches. Trinidad has the last remaining population of manatees among the eastern Caribbean islands, which is composed of a small number of individuals confined to a small swamp. We compared the history, patterns, and results of this exploitation in Trinidad and Tobago with other neighbouring nations (Venezuela, Grenada, and St. Vincent and the Grenadines). As in other countries in the area that practised intense whaling, local populations of humpback whales have become virtually extinct in their waters. Culture, more than anything else, seems to be the force shaping the nature of marine mammal exploitation in the Caribbean, which has resulted in different histories and methods of exploitation for each one of the countries studied.